The herd : a novel - Bartz, Andrea (Ballantine Books, 2020)
"The name of the elite, women-only coworking space stretches across the wall behind the check-in desk: THE HERD, the H-E-R always in purple. In-the-know New Yorkers crawl over each other to apply for membership to this community that prides itself on mentorship and empowerment. Among the hopefuls is Katie Bradley, who's just returned from the Midwest after a stint of book research blew up in her face. Luckily, Katie has an "in," thanks to her sister Hana, an original Herder and the best friend of Eleanor Gleason, its charismatic founder. Eleanor is a queen among The Herd's sun-filled rooms, admired and quietly feared, even as she strives to be warm and approachable. As head of PR, Hana is working around the clock in preparation for a huge announcement from Eleanor--one that would change the trajectory of The Herd forever. Though Katie loves her sister's crew, she secretly hopes she's found her next book subject in Eleanor, who's brilliant, trailblazing--and extremely private. Then, on the night of the glitzy Herd news conference, Eleanor vanishes without a trace. Everybody has a theory about what made Eleanor run, but when the police suspect foul play, everyone is a suspect: Eleanor's husband, other Herders, the men's rights groups that have had it out for The Herd since its launch--even Eleanor's closest friends. As Hana struggles to figure out what her friend was hiding and Katie chases the story of her life, the sisters must face down the secrets they're keeping from each other--and confront just how dangerous it can be when women's perfect veneers start to crack, crumble, and then fall away all together"--